Sino-American relations challenges ahead - Hao, Yufan (Ashgate Pub., 2010)
More than thirty years have passed since the normalization of Sino-American relations in 1979. This volume analyzes the problems and issues in Sino-American relations in the context of regional and global strategic patterns and their historical development in the last thirty years.